Raman Imaging Techniques and Applications - Zoubir, Arnaud; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Raman imaging has long been used to probe the chemical nature of a sample, providing information on molecular orientation, symmetry and structure with sub-micron spatial resolution. Recent technical developments have pushed the limits of micro-Raman microscopy, enabling the acquisition of Raman spectra with unprecedented speed, and opening a pathway to fast chemical imaging for many applications from material science and semiconductors to pharmaceutical drug development and cell biology, and even art and forensic science. The promise of tip-enhanced raman spectroscopy (TERS) and near-field techniques is pushing the envelope even further by breaking the limit of diffraction and enabling nano-Raman microscopy.
Instrumentation: -- Theory and instrumentation -- Imaging modes -- Micro-Raman Applications: -- Raman imaging in Semiconductor Physics and its application in Microelectronics -- Raman optimization of the properties of nano-phased materials -- Raman Imaging of meso- and nano-strutured materials -- Application of Raman-based images in the Earth sciences -- Uses of Raman Mapping and Imaging in Pharmaceutical Forensics -- Raman Microscopy: A Versatile Approach to Bio-imaging -- Mapping chemical and structural composition of biological and pharmaceutical samples by Raman and Surface-enhanced Raman scattering (SERS) spectroscopy -- Morphology and Chemical Structure: Agricultural Applications -- Tip-Enhanced Raman Spectroscopy: -- From stress and dopant distribution mappings in solar cells to applications of the surface enhanced Raman effect -- Tip-enhanced Raman and photoluminescence of nanotubes -- CARS spectroscopy, implementation to far-field and near-filed microscopy and applications.
Keywords: Physics; Chemistry, Physical organic; Microscopy; Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Physical Chemistry; Biological Microscopy